1993
DOI: 10.1088/0953-2048/6/8/005
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of pool boiling heat transfer from ceramic Y1Ba2Cu3O7- deltasuperconductors to liquid nitrogen

Abstract: We present measurements of pool boiling heat transfer from ceramic Y,Ba,Cu,O,_, to liquid nitrogen in the range of heat flux density up to q. = 35 W cm-'. Along the convective pool boiling regime, a linear relationship between the interface overtemperature, T w , andq, has been observed, with a value of the heat transfercoefficienth = 1.3 W cm-' K-'. In the nucleate regime, the q. dependence on T, follows quite well a power law, with an exponent close to 0.7. In the low heat flux regime (9, 5 5 W cm-'), the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In low pressure cryogenic gas or in vacuum, the convective heat transfer coefficient is small, as an example a value of 1.94 W/m²K is reported in [62] while when in cryogenics fluids, it can be several orders of magnitude larger. In addition, in liquids, several heat draining regimes exist (free convection, nucleate boiling, transition boiling and film boiling) which correspond to several overall convective heat transfer coefficients [64]. In the case of liquid nitrogen, the convective heat transfer coefficient equals 2000 W/m²K for small temperature differences between the coolant and the superconductor and it can increase to values of 13000 W/m²K for larger temperature differences [10,[63][64].…”
Section: Theory/calculationmentioning
confidence: 99%
“…In low pressure cryogenic gas or in vacuum, the convective heat transfer coefficient is small, as an example a value of 1.94 W/m²K is reported in [62] while when in cryogenics fluids, it can be several orders of magnitude larger. In addition, in liquids, several heat draining regimes exist (free convection, nucleate boiling, transition boiling and film boiling) which correspond to several overall convective heat transfer coefficients [64]. In the case of liquid nitrogen, the convective heat transfer coefficient equals 2000 W/m²K for small temperature differences between the coolant and the superconductor and it can increase to values of 13000 W/m²K for larger temperature differences [10,[63][64].…”
Section: Theory/calculationmentioning
confidence: 99%
“…Since all of the calculated cooling rates are much lower than that needed for the vitrification of pure water (roughly 1 Million °C/sec), our model indicates that in order to minimize CPA it is very important to plunge the quartz micro-capillary as fast as possible into the cryogenic medium (liquid nitrogen) during cooling to create a forced impinging convective flow of liquid nitrogen around the quartz microcapillary to enhance the boiling heat transfer coefficient at the boundary (Figure 2). It was reported that the heat transfer coefficient for such a forced convective boiling flow of liquid nitrogen are generally higher than 2000 W m −2 °C −1 and can be higher than 10,000 W m −2 °C −1 [24,33,39,41]. When the boiling heat transfer coefficient is in the range of 2,000 to 10,000 W m −2 °C −1 , the predicted cooling rates for the open pulled straw and the traditional straw are around 20,000 and 3,000 °C/min, respectively.…”
Section: Thermal Analysis Of Cooling Ratesmentioning
confidence: 99%
“…The superconducting microbridge exchanges heat mainly with its substrate, because at the operation temperatures, around 90 K, the heat transfer coefficient between YBCO films, for instance, and their substrate is h bs ≈ 10 3 Wcm −2 K, whereas through liquid nitrogen or between the substrate and the copper holder they are 1000 times less Lorenzo et al, 2009;Mosqueira et al, 1993). Hence, the conditions for a good refrigeration and, therefore, an optimal operation of the limiting device, depend very much on the relative dimensions of the microbridge and their substrate.…”
Section: Superconducting Fault Current Microlimitersmentioning
confidence: 99%